KEKURANGAN ENERGI KRONIS DAN ANEMIA SEBAGAI FAKTOR RISIKO BAYI BERAT LAHIR RENDAH - Mahmudah, Mahmudah; Dewi, Vonny Khresna; Kristiana, Efi; Isnaniah, Isnaniah (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Low Birth Weight (LBW) is a public health problem, both short-term and long-term, and remains a leading cause of perinatal morbidity and mortality. The incidence of LBW at the Amuntai Selatan Community Health Center in 2024 was 9.52%. Factors directly influencing the incidence of LBW are poor nutritional status during pregnancy, or Chronic Energy Deficiency (CED), and anemia during pregnancy. Objective: To find out the correlations between CED and anemia with the incidence of LBW at the South Amuntai Health Center. Method: This study used an observational analytical design with a case-control approach. The sampling technique used simple random sampling with a ratio of 40 cases:80 controls. The independent variable was the incidence of low birth weight (LBW), and the dependent variables were CED and anemia. Data collection used secondary data. Data analysis used the Chi-Square test. Result: A total of 40 mothers (33.3%) gave birth and experienced low birth weight (LBW). A total of 25 mothers (20.8%) experienced chronic energy deficiency (CED). A total of 13 mothers (10.8%) experienced anemia. There was a correlation between CED (P-value 0.026, OR 2,728) and anemia (P-value 0.022, OR 3,750) with the incidence of LBW at the Amuntai Selatan Community Health Center. Conclusion: It is important for mothers to undergo regular checkups during pregnancy and maintain their nutritional status by consuming a varied diet and regularly taking iron supplements.